Integrating pharmacogenomics into the electronic health record by implementing genomic indicators. (7th October 2019) - Caraballo, Pedro J; Sutton, Joseph A; Giri, Jyothsna; Wright, Jessica A; Nicholson, Wayne T; Kullo, Iftikhar J; Parkulo, Mark A; Bielinski, Suzette J; Moyer, Ann M
Abstract: Pharmacogenomics (PGx) clinical decision support integrated into the electronic health record (EHR) has the potential to provide relevant knowledge to clinicians to enable individualized care. However, past experience implementing PGx clinical decision support into multiple EHR platforms has identified important clinical, procedural, and technical challenges. Commercial EHRs have been widely criticized for the lack of readiness to implement precision medicine. Herein, we share our experiences and lessons learned implementing new EHR functionality charting PGx phenotypes in a unique repository, genomic indicators, instead of using the problem or allergy list. The Gen-Ind has additional features including a brief description of the clinical impact, a hyperlink to the original laboratory report, and links to additional educational resources. The automatic generation of genomic indicators from interfaced PGx test results facilitates implementation and long-term maintenance of PGx data in the EHR and can be used as criteria for synchronous and asynchronous CDS.